The Roles of Green Perceived Value, Green Perceived Risk, and Green Trust towards Green Purchase Intention of Inverter Air Conditioner in Surabaya - Felix Aprilio Rahardjo (iBuss Management, 2015)
Environmental degradation keeps  increasing every year and global warming is one of the environmental degradations that we need to face right now. The fact is air conditioner is one of the main causes of global warming. This research is done to know the impact of green perceived value and green perceived risk towards green purchase intention of inverter air conditioner in Surabaya, through the mediation of green trust. In this research, there are two independent variables and one dependent variable involved. The independent variables are  green perceived value and green perceived risk, while the dependent variable  green purchase intention.In this research, there  are  250 questionnaires distributed with clustered  sampling method system. The analysis technique used in this research is structural equation modelling (SEM), supported with SPSS and AMOS as a tools for data analysis. The research result indicates that green perceived value will have a positive significant impact towards green purchase intention of low watt inverter air conditioner in Surabaya partially mediated by green trust. Furthermore, green perceived risk will have a negative significant impact towards green purchase intention of inverter air conditioner in Surabaya fully mediated by green trust.  Keywords: Green Perceived Value, Green Perceived Risk, Green Trust, Green Purchase Intention, Inverter Air Conditioner